Significance of Artificial Intelligence and Machine Learning in Business Enterprises - Chander Diwaker; Atul Sharma (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The rising demand for Artificial Intelligence (AI) and Machine Learning (ML) technologies in the corporate sector offers significant opportunity for firms to foster innovation and change. Incorporating generative AI capabilities into AI/ML corporate adoption plans can significantly improve the performance and efficacy of these technologies. By adopting AI/ML with generative AI functionalities, organizations may optimize content production workflows, provide synthetic data to enhance ML model training, and provide more captivating consumer experiences. This connection enhances creativity and innovation, accelerating model development and refinement, leading to expedited advancement in the creation of sophisticated AI systems. This article discusses the significance of AI and ML in business. Future trends and difficulties are also examined.